2000
DOI: 10.1007/s001040051019
|View full text |Cite
|
Sign up to set email alerts
|

Deciduose der Appendix

Abstract: Deciduosis of the appendix is a rare cause of acute appendicitis in pregnancy. Ectopic decidual cells localized in the submesothelial stroma may represent a physiologic reaction of the pluripotent stromal cells to progestational hormonal stimulation. Less frequently, deciduosis is based on a preexisting extragenital endometriosis, visible in a localization other than strictly submesothelial, in residuals of cyclic proliferation and bleeding, and in endometrial glandular formations embedded in the decidual cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
4
0
10
Order By: Relevance
“…The lesion infiltrates the serosal surface of all abdominal viscera, as occurs in carcinomatosis from metastatic adenocarcinomas, squamous cell carcinomas, and malignant deciduoid mesothelioma. 16,23,25 Decidualized endometrial stromal cells observed on a Papanicoloau smear may confound diagnosis of a cervical intraepithelial neoplasia. 9 Rarely, decidualized aberrant stroma or endometriosis tissue may also directly complicate pregnancy through hemoperitoneum, intestinal perforation, or pneumothorax.…”
mentioning
confidence: 99%
“…The lesion infiltrates the serosal surface of all abdominal viscera, as occurs in carcinomatosis from metastatic adenocarcinomas, squamous cell carcinomas, and malignant deciduoid mesothelioma. 16,23,25 Decidualized endometrial stromal cells observed on a Papanicoloau smear may confound diagnosis of a cervical intraepithelial neoplasia. 9 Rarely, decidualized aberrant stroma or endometriosis tissue may also directly complicate pregnancy through hemoperitoneum, intestinal perforation, or pneumothorax.…”
mentioning
confidence: 99%
“…Differential diagnosis of acute appendicitis may provide various conditions: (I) medical emergencies (porphyria, dia- betic ketoacidosis, glomerulonephritis, pyelonephritis); (II) gynecological emergencies (overian cyst rupture, tubaovarian abscess, fallopian tube torsion); (III) non-gynecological emergencies (mesenteric lymphadenitis, acute cholecystitis, acute pancreatitis, peptic ulcus perforation, intestinal obstruction); and (IV) obstetrical emergencies (preterm labor, ectopic pregnancy, preeclampsia) [3,25]. In our study, urological, gynecological, and intestinal conditions were investigated in the differential diagnosis, and appropriate treatments were performed accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic deciduosis is a known phenomenon, described in different locations as cervix uteri [8], ovary [9], fallopian tubes, appendix [10], peritoneum [6], omentum [4], diaphragm, liver, spleen, pleura [11], lymph nodes [12], renal pelvis [13], skin [14]. Clinically extra uterine ectopic deciduosis may easily simulate disseminated tuberculosis [3] or metastatic disease [2].…”
Section: Discussionmentioning
confidence: 99%